The Concept of Logic by E. Nagel - Petkevičiūtė, Nijolė (Problemos, 1984)
The idea of universal logic is characteristic of the gnoseology of the 17th and 18th centuries. In the second half of the 19th century in close relationship with the development of logics and the formation of mathematical logics the problem of the origins of logics has arisen. Neopositivism discusses the problem in the context of Kant’s dichotomy of synthetic and analytic propositions and relates the rules of logic to the latter sort of propositions. E. Nagel takes the same position. In opposition to the descriptive and ontological conception of logics he tried to create “logic without an ontology”, but naturalistic origins of his philosophy undermined such an attempt. This explains why his neopositivistic solution of the problem is supplemented by instrumentalist statements and the inference of some kind of link between logical principles and the object is made.